1999
DOI: 10.1046/j.1365-2559.1999.00712.x
|View full text |Cite
|
Sign up to set email alerts
|

CD44v6 expression in inflammatory bowel disease is associated with activity detected by endoscopy and pathological features

Abstract: CD44v6 expression in IBD is significantly associated with activity detected by means of endoscopy and pathological features. Our data suggest that CD44v6 expression may have some usefulness in conjunction with other factors as a means of evaluating the disease activity. Moreover, CD44v6 expression was higher in ulcerative colitis than Crohn's disease (P = 0.02), although this does not confirm the utility of monoclonal antibody 2F10 in differential diagnosis between ulcerative colitis and Crohn's disease, as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
2
6
0
Order By: Relevance
“…Further analysis revealed binding of GM35 to a v6-containing variant of CD44 (CD44v6). The expression of CD44v6 in epithelial cells reported in the current work is supported by previous studies which report that alternative splicing of CD44 is mediated by tissue-specific factors with certain variant exon products being differentially expressed (or at least predominantly found) on defined tissues such as epithelium (4548). Further, the expression of the GM35 ligand in T84 and HT29 cells but not in other epithelial cell lines is in keeping with its binding to CD44v6 as it has been reported that this large, heavily glycosylated protein is expressed in these epithelial cell lines but not in Caco2 colon cells (37).…”
Section: Discussionsupporting
confidence: 89%
“…Further analysis revealed binding of GM35 to a v6-containing variant of CD44 (CD44v6). The expression of CD44v6 in epithelial cells reported in the current work is supported by previous studies which report that alternative splicing of CD44 is mediated by tissue-specific factors with certain variant exon products being differentially expressed (or at least predominantly found) on defined tissues such as epithelium (4548). Further, the expression of the GM35 ligand in T84 and HT29 cells but not in other epithelial cell lines is in keeping with its binding to CD44v6 as it has been reported that this large, heavily glycosylated protein is expressed in these epithelial cell lines but not in Caco2 colon cells (37).…”
Section: Discussionsupporting
confidence: 89%
“…Similar colocalization of sLe a and CD44v6 has been reported in inflamed cervical cells and IECs (7,20). The importance of CD44v6 as a marker of epithelial stress is further highlighted by studies showing that CD44v6 expression is restricted to inflamed or squamous epithelia (21,22), and that epithelial CD44v6 expression strongly associates with disease activity in ulcerative colitis (23,24).…”
Section: Discussionsupporting
confidence: 64%
“…In an inflammatory bowel disease (IBD) model, expression of CD44v7 is crucial for colonic inflammation ( 210 , 211 ). Furthermore, CD44v6 expression is associated with IBD severity in patients ( 212 – 214 ). Extensive HA matrix accumulates in bleomycin-induced lung fibrosis in CD44-null mice with persistent lung inflammation, extended chemokine production, impaired clearance of apoptotic lymphocytes, and death ( 215 ).…”
Section: Interaction Of Cd44 and Rhamm With Hamentioning
confidence: 99%